PENYEBAB DAN SERANGGA VEKTOR PENYAKIT KERITING PADA TANAMAN LADA - RODIAH BALFAS; SUPRIADI SUPRIADI; T. L. MARDININGSIH; ENDANG SUGANDI (Pusat Penelitian dan Pengembangan Perkebunan, 2002)
The cause of stunting disease of black pepper (Piper nigrum) in Indonesia has not yet been confirmed cither due o a virus or mycoplaam. However, similar disease found on black pepper plants in the Southeast Asia is caused by Piper yellow mottle virus (PYMV) which is transmitted by Planococcus citri. This expeiments was aimed o examine the cause of the stunting disease and its insect vectors. The expeiment were conducted from October 1998 to May 2001. Diseased vegetative materials of black pepper plants showing stunting disease were collected from Sukamulya, Sukabumi. The potential insect vectors were collected from black pepper plants in Bogor, IP Sukamulya (Sukabumi), Lampung and Bangka. The insects were fed on the diseased plants obtained from Lampung, Bogor and IP Sukamulya, then transferred o the healthy plants. The healthy plants were produced rom true seeds and cutings oiginated rom Bogor and IP Sukamulya. The tested plants were incubated at the green house and examined for disease development. Diseased leaf samples collected rom black pepper plant rom IP. Sukamulya and the transmitted plants were sent to the University of Minnesota, USA for Ihe virus (PYMV) by using ISEM (immunosorbent electron microscope). The result snowed that the leaves samples rom IP. Sukamulya were infected by PYMV. The morphology and size of the virus were similar to those caused stunting disease in the South East Asia. Potential insects vectors found on the diseased black pepper plants were two mealybugs, P. minor and Ferrisia virgata (Hemiptera; Coccoidca: PaaidbcoccidaeX aa well as an aphid Toxoptera aurantii (Hemiptera: Aphidoidea: Aphididae). The first tial on disease transmission by using P. minor, previously reared on the potato tubers, showed one out of ten tested plants produced disease sympom. The subsequent trial using P minor, bred on healthy black pepper seedlings, showed thee out often tested plants developed disease symptoms. None of the aphid transmitted plants developed Ihe disease. This study confirmed thai PYMV b the cause of stunting disease on black pepper in IP Sukamulya and Lampung and P. minor as the insect vecor of the disease.